1997
DOI: 10.1097/00005373-199711000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Command-Physician in Trauma Resuscitation

Abstract: An identified command-physician enhances trauma resuscitation performance. Completion of the primary and secondary survey is not affected by the physician combination. Prompt formulation of a definitive plan is facilitated by the active involvement of an attending traumatologist or a properly mentored trauma fellow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 8 publications
1
63
0
3
Order By: Relevance
“…Disagreements over procedures, confusion over team leadership, organizational chaos or demeaning comments represent poor team dynamics and can cause a team to lose focus. Team leaders often do not (or will not) follow basic protocols [47][48][49]. Medical errors tend to occur more frequently in stochastic environments or when team dynamics and communication are flawed [18,[50][51][52][53].…”
Section: Team Focus and Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disagreements over procedures, confusion over team leadership, organizational chaos or demeaning comments represent poor team dynamics and can cause a team to lose focus. Team leaders often do not (or will not) follow basic protocols [47][48][49]. Medical errors tend to occur more frequently in stochastic environments or when team dynamics and communication are flawed [18,[50][51][52][53].…”
Section: Team Focus and Errorsmentioning
confidence: 99%
“…With the code team, processes and procedures that are organized, disciplined and controlled are generally less stressful to the participants [60,[64][65][66]. The resuscitation team leader sets the tone for the team and prevents unnecessary stress levels [49].…”
Section: Team Focus and Errorsmentioning
confidence: 99%
“…Only recently has medicine started to recognize this fact, and started teaching physicians to be effective team leaders (Howard et al 1992;Reznek et al 2003;Marsch et al 2004). It has been shown that teams who function with an effective team leader adhere more closely to established protocols, sustain fewer medical errors, and as a result, have a more favourable outcome for their patients, both simulated and real (Hoff et al 1997;Cooper & Wakelam 1999;Morey et al 2002;Devita et al 2004Devita et al , 2005Marsch et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…22 The most common causes of spinal cord injuries are motor vehicle crashes (48%), falls (21%), assaults (15%) and sports-related accidents (14%). 4 It is imperative that the practitioner be aware of the possibility of spinal cord injury in the multiply injured patient. Of all trauma patients that die within the first 30 minutes after injury, 20-25% have a cervical SCI.…”
Section: Concurrent Spinal Injurymentioning
confidence: 99%